Go tell the bees that i am gone eaudiobook - Gabaldon, Diana (Outlander, 2021)
#1 New York Times bestselling author Diana Gabaldon returns with the newest novel in the epic Outlander series. The past may seem the safest place to be ... but it is the most dangerous time to be alive. ...Jamie Fraser and Claire Randall were torn apart by the Jacobite Rising in 1746, and it took them twenty years to find each other again. Now the American Revolution threatens to do the same. It is 1779 and Claire and Jamie are at last reunited with their daughter, Brianna, her husband, Roger, and their children on Fraser's Ridge. Having the family together is a dream the Frasers had thought impossible. Yet even in the North Carolina backcountry, the effects of war are being felt. Tensions in the Colonies are great and local feelings run hot enough to boil Hell's teakettle. Jamie knows loyalties among his tenants are split and it won't be long until the war is on his doorstep. Brianna and Roger have their own worry: that the dangers that provoked their escape from the twentieth century might catch up to them. Sometimes they question whether risking the perils of the 1700s—among them disease, starvation, and an impending war—was indeed the safer choice for their family. Not so far away, young William Ransom is still coming to terms with the discovery of his true father's identity—and thus his own—and Lord John Grey has reconciliations to make, and dangers to meet ... on his son's behalf, and his own. Meanwhile, the Revolutionary War creeps ever closer to Fraser's Ridge. And with the family finally together, Jamie and Claire have more at stake than ever before.